Laboratory Control of Oral Anticoagulants - Loeliger, E. A; Meuwisse-Braun, J. B; Muis, H; Buitendijk, F. J. J; Veltkamp, J. J; Hemker, H. C (Thrombosis and Haemostasis, 1970)
The therapeutic range in oral anticoagulation, which is defined as the range of hypocoagulability resulting in optimal thrombosis prophylaxis and an acceptable bleeding tendency, is monitored by assay procedures of which the majority are modifications of Quick’s original prothrombin time test. With respect to individual patients on stabilized anticoagulation, the different modifications commonly used give the same information, the reliability depending more on the accuracy than on the sensitivity of the tests. The results do not appear to be comparable in terms of conventional reference curves or prolongation ratios of the coagulation times found, but on the basis of painstakingly defined normal and patient plasma, the mean of the factor II and factor X activity present in patients’ plasma proved to be a useful common denominator. In terms of this common denominator, the therapeutic range to be aimed at lies between (8 to) 10 and 20(to 25)percent.